RELEVANSI DEBT TO EQUITY RATIO DAN PERTUMBUHAN PENJUALAN TERHADAP RETURN ON ASSET PERUSAHAAN RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Furniawan (Universitas La Tansa Mashiro, 2024)
Financial performance is an analysis conducted to assess how well a company operates its business by adhering to sound financial rules. It reflects the company's achievements over a period, including capital adequacy, liquidity, and profitability. This study aims to analyze the impact of capital structure and sales growth on the performance of retail companies listed on the Indonesia Stock Exchange (IDX). The study population comprises retail companies listed on the IDX. The sample was determined using purposive sampling based on specific criteria, resulting in 14 companies with 70 financial report data points. Secondary data were utilized, and multiple linear regression analysis was conducted using SPSS 20. The results indicate that capital structure (DER) negatively and significantly affects performance (ROA), while sales growth positively and significantly impacts performance. Together, capital structure and sales growth positively and significantly influence company performance. Future researchers are advised to expand the sample of companies listed on the IDX and consider using Debt to Asset Ratio (DAR) to measure the relationship between total debt and total assets. This variable is considered more relevant to improving company performance.